Juridical review of womb renting in the realm of civil law (comparation study of Indian and Indonesian countries) - I Made Krisnan Wijaya Putra; Putu Eka Trisna Dewi (Institute Of computer Science (IOCS), 2024)
This piece of work aims to go more into the rules and laws of India and Indonesia as they pertain to the practice of renting a woman's womb. Research in descriptive normative juridical law is used in the writing process. Through library and document studies, legal material analysis procedures utilizing the syllogism approach, which employs a deductive mentality, and other ways, both primary and secondary legal resources are consulted. Since surrogacy is often a couple's final resort for starting a family, this piece concludes that infertility is the primary motivation for using it. An agreement is necessary for womb renting to commence. Womb rental is quite similar to in vitro fertilization (IVF), with the main exception being that the embryo is transported to the uterus of another person. Indonesian health standards do not permit womb renting, and contracts for such services are void according to Indonesian law because they do not adhere to one of the requirements for contract validity outlined in the Civil Code. Commercial womb rental was formerly legal in India, but the country outlawed the practice because to the high number of surrogate moms who were abandoned. However, surrogacy could still be done voluntarily under certain circumstances.